Body Consciousness in the Healthcare Environment - Line Joranger (Phenomenology & Practice, 2023)
Like the human mind, the human body is the medium by which we represent ourselves, whether we are patients or healthcare providers. This paper concerns the significance of understanding the existential phenomenological side of a patient’s body within healthcare. To care for a patient’s body, one needs to be aware of how the body appears to itself, to others, and in a lager environmental reality.  We think and feel and observe the world with our body, especially with the brain and nervous system, but also with other dimensions of the body manifesting itself as a somatic tonus. The healthcare providers’ body does not only represent a profession, but also who they are as a person and what kind of environment they are affected by. The same applies to the patients' body. As a tool for experiencing, a tool inseparable from our very being, our physical body functions as a surface open to and in contact with the healthcare environment that surrounds it. In the modern healthcare regime, the human body is nearly always visible and under constant surveillance. In the environment of control and visibility bodies become psychologized and normalized to fit into sociocultural demands of economic adaption, social participation, and communication, which in certain situations seem hostile to the ideology of care, freedom, and humanity. We should realize that all our ethical concepts and norms, even the very notion of humanity that underwrites them, depend on social forms of life involving the ways we experience our bodies in different medical and sociocultural situations.